An embedding algorithm for multiple watermarks - Shieh, CS; Huang, HC; Wang, FH; Pan, JS (My University, 2003)
A new algorithm for embedding several watermarks into the same original source is proposed in this paper. Instead of conventional watermark embedding algorithms that embed one watermark in one specific domain, we propose algorithms for embedding multiple watermarks into different compression domains to protect the ownership of the original images. The proposed schemes for embedding and extraction in different domains vary from the existing methods reported in the literature. Simulation results show their robustness for surviving intentional attacks and, hence, their effectiveness in protecting copyrights. They are also easy to implement.
Keywords: digital watermark; vector quantization (VQ); discrete cosine transform (DCT); joint photographic experts group (JPEG); secret key; blind detection; Stirmark